Splenic and portal venous flow associated with frailty and sarcopenia in older outpatients with cardiovascular disease - Joji Ishikawa; Shutaro Futami; Ayumi Toba; Aya Yamamoto; Keisho Kobayashi; Kana Takani; Hideko Ono; Teppei Maeda; Masuyo Kawano; Masaru Kiyomizu; Yoshiaki Tamura; Atsushi Araki; et al. (BMC Geriatrics)
Abstract Background Older patients with cardiovascular disease often experience frailty and sarcopenia. We evaluated whether a reduced blood flow in the splenic and portal vein is associated with frailty and sarcopenia in older patients with cardiovascular disease. Methods Blood flow in the splenic and portal vein was evaluated using EPIQ7 (Philips) in older patients (aged ≥ 65 years, 123 patients) with cardiovascular disease, who visited the frailty outpatient clinic. Frailty was assessed using the Japanese version of Cardiovascular Health Study (J-CHS) criteria and the Kihon Checklist (KCL), while sarcopenia was assessed using the Asian Working Group of Sarcopenia 2019 criteria. Results The mean age of the patients was 81.6 ± 6.6 years (42.3% female). Frailty was observed in 34.2% of patients using the J-CHS criteria and 36.9% using the KCL criteria, while severe sarcopenia was identified in 20.2% of patients. In the KCL criteria, the splenic venous flow decreased with the severity of frailty (248.3 ± 148.4, 202.1 ± 177.9, 139.2 ± 81.1 mL/min, P = 0.007), Additionally, the splenic venous flow was significantly lower in frail patients than in robust patients (P = 0.006). This association remained significant even after adjusting for confounding factors such as age, sex, body mass index, habitual drinking, smoking history, diabetes, dyslipidemia, hypertension, systolic blood pressure, atrial fibrillation, heart failure, and history of stroke (P = 0.039). In a parallel analysis, the splenic venous flow was remarkably decreased in patients with sarcopenia (232.0 ± 172.8 vs. 145.0 ± 91.9 mL/min, P = 0.003); however, no significant relationship was found between the severity of frailty and splenic venous flow according to the J-CHS criteria (P = 0.159). Among the J-CHS criteria sub-items, the splenic venous flow was decreased in patients with a decreased appendicular skeletal muscle index (ASMI) (332.9 ± 41.6 vs. 98.5 ± 43.5 mL/min, P = 0.005); however, there was no significant difference in the splenic venous flow between patients with and without decreased walking speed (P = 0.064) or reduced grip strength (P = 0.369). The portal venous flow was not significantly associated with frailty or sarcopenia. Conclusion In older patients with cardiovascular disease, a decreased splenic venous flow was observed in those with frailty by the KCL criteria, those with sarcopenia, and those with a decreased ASMI.